How Does Financial Sector Reacts After Special Events? An Event Study Analysis of Tunisia after the Revolution of 2011. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Using an event study analysis, we aim to investigate the impact of political, economic, social and terrorism events, on the Tunisian financial sector, over the period of the Tunisian Revolution; from (12)2010 to (04)2014. Based on a daily data analysis using three selected variables ; Sectoral index of performance of Tunisian banks ,Index of Tunisian stock market and the exchange rate Euro/ Dinar,  the EGARCH model results have highlighted that general events decrease the return of our variables, and increase their volatility. More, results have shown that stock market is very sensitive to political and terrorism events, bad economic events increase the volatility of the exchange rate, and decrease the performance of banking sector. Political events remain the more important component, they affect negatively all the endogenous variables; coefficients in the mean equation show an important decline in term of the return of banking sector ,the stock market and the exchange rate.